Evaluation of existing guidelines for their adequacy for the microbial characterisation and environmental risk assessment of microorganisms obtained through synthetic biology. (28th October 2020) - ,; More, Simon; Bampidis, Vasileios; Benford, Diane; Bragard, Claude; Halldorsson, Thorhallur; Hernández‐Jerez, Antonio; Susanne, Hougaard Bennekou; Koutsoumanis, Kostas; Machera, Kyriaki; Naegeli, Hanspeter; Nielsen, Søren Saxmose; et al.
Abstract: EFSA was asked by the European Commission to consider synthetic biology developments for agri‐food use in the near future and to determine if the use of this technology is expected to constitute potential risks and hazards for the environment. Moreover, EFSA was requested to evaluate the adequacy of existing guidelines for risk assessment and if updated guidance is needed. The scope of this Opinion covers viable synthetic biology microorganisms (SynBioMs) expected to be deliberately released into the environment. The evaluation was based on: (i) horizon scanning of published information, (ii) gap analysis of existing guidelines covering the scope of this mandate, and (iii) future outlooks. A horizon scan showed that SynBioM applications could be ready for deliberate release into the environment of the EU in the next decade. However, extensively engineered SynBioMs are only expected in the wider future. For the microbial characterisation and the environmental risk assessment, the existing EFSA Guidances are useful as a basis. The extent to which existing Guidances can be used depends on the familiarity of the SynBioM with non‐modified organisms. Among the recommendations for updated Guidance, the range of uses of products to be assessed covering all agri‐food uses and taking into account all types of microorganisms, their relevant exposure routes and receiving environments. It is suggested that new EFSA Guidances address all 'specific areas of risk' as per Directive 2001/18/EC. No novel environmental hazards are expected for current and near future SynBioMs. However, the efficacy by which the SynBioMs interact with the environment may differ. This could lead to increased exposure and risk. Novel hazards connected with the development of xenobionts may be expected in the wider future. Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2020.EN-1934/full